1978
DOI: 10.1136/vr.102.2.27
|View full text |Cite
|
Sign up to set email alerts
|

The effect of xylazine and xylazine followed by insulin on blood glucose and insulin in the dairy cow

Abstract: The effect of xylazine and xylazine followed 20 minutes later by insulin upon glucose metabolism and plasma insulin concentrations was examined in three cows. After doses of 0.18 mg per kg xylazine given intramuscularly (IM) or 0.15 mg per kg given intravenously (IV) hepatic glucose production increased, plasma insulin concentrations decreased to 25 to 33 per cent of control values, and there was a prolonged hyperglycaemia. When 200 units of soluble insulin were given 20 minutes after similar doses of xylazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
22
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…It has been reported that intravenous xylazine treatments increased glucose production directly on the liver in cattle [11]. In addition, xylazine has been reported to increase glucagon release from the pancreas in sheep [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that intravenous xylazine treatments increased glucose production directly on the liver in cattle [11]. In addition, xylazine has been reported to increase glucagon release from the pancreas in sheep [8].…”
Section: Discussionmentioning
confidence: 99%
“…We also reported that xylazine injection resulted in a GH increase in cattle [6] as in dogs [5]. Xylazine is also known to induce hypoinsulinemia and hyperglycemia in ruminants [6][7][8][9][10][11] but, as far as we know, no mechanism of xylazine-induced GH release has ever been reported in any animal species. It is likely that a2-adrenergic receptors regulate the response of GH to xylazine injection, since xylazine-induced sedation is mediated by a2-adrenoceptors [4].…”
mentioning
confidence: 99%
“…Coadministration of ketamine with xylazine [ketamine/xylazine anesthesia (KX)] is commonly used in laboratory animals such as mice and rats to induce anesthesia and to enable surgical interventions to induce disease and develop animal models of human diseases. It has been reported that administration of xylazine alone or in combination with ketamine may cause hyperglycemia in dogs and cattle (Symonds and Mallinson, 1978;Goldfine and Arieff, 1979). Recently, we have demonstrated that KX produces acute hyperglycemia in fed rats and may be used as an animal model of acute hyperglycemia to test the efficacy and mechanism of glucoregulatory and other therapeutic agents (Saha et al, 2005b).…”
mentioning
confidence: 99%
“…It has become widely employed for veterinary clinical use and has proven to be relatively safe when used alone or in combination with other tranquilizers and anesthetics. It has been reported that the drug induced hyperglycemia and hypoinsulinemia in domestic animals [6][7][8][9][10]. However, the effects of xylazine on GH In the present study, we investigated the effects of xylazine injection on plasma GH and IGF-I concentrations and confirmed xylazine-induced hyperglycemia and hypoinsulinemia to monitor the action of the drug in calves.…”
mentioning
confidence: 73%
“…to calves caused a significant doserelated increase in plasma glucose concentration. Symonds and Mallinson [10] reported that intravenous xylazine treatments increased hepatic glucose production. It has been reported that xylazine injection increased glucagon release from the pancreas in sheep [7].…”
Section: Discussionmentioning
confidence: 99%